1998
DOI: 10.1006/fgbi.1998.1059
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis and Membrane Turnover in the Germ Tube ofUromyces fabae

Abstract: Hoffmann, J. and Mendgen, K. 1998. Endocytosis and membrane turnover in the germ tube of Uromyces fabae. Fungal Genetics and Biology 24, 77-85. We have used the fluorescent dye FM4-64 as a tracer to demonstrate bulk membrane internalization (endocytosis) and redistribution of the dye within the cytoplasm of the germ tube of the rust fungus Uromyces fabae. Staining of the hyphal membrane was detected 4 s after application of FM4-64 and reached a maximum after 1 min. The highest fluorescence intensity occurred i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 30 publications
3
49
0
Order By: Relevance
“…In filamentous fungi, the endocytotic pathway may be required for polarized growth because of the need for membrane recycling. This has been strongly implied from studies in Ustilago maydis (Wedlich-Söldner et al, 2000) and Uromyces fabae (Hoffmann and Mendgen, 1998).…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…In filamentous fungi, the endocytotic pathway may be required for polarized growth because of the need for membrane recycling. This has been strongly implied from studies in Ustilago maydis (Wedlich-Söldner et al, 2000) and Uromyces fabae (Hoffmann and Mendgen, 1998).…”
mentioning
confidence: 72%
“…In filamentous fungi, the endocytotic pathway may be required for polarized growth because of the need for membrane recycling. This has been strongly implied from studies in Ustilago maydis (Wedlich-Söldner et al, 2000) and Uromyces fabae (Hoffmann and Mendgen, 1998).Membrane recycling may be particularly important during the very rapid transition in growth that accompanies penetration peg formation and the release of appressorial turgor. If PDE1 is required for the efficient movement and docking of endosomal vesicles, then this too might account for its requirement in penetration peg formation.…”
mentioning
confidence: 92%
“…Pioneering studies of the endocytic pathway in the yeast Saccharomyces cerevisiae have shown that the amphiphilic styryl dye FM4-64 is internalized by endocytosis and is delivered to the fungal vacuole via the endocytic pathway (127). Surprisingly, similar studies in filamentous fungi have demonstrated that FM4-64 transiently stains the Spitzenkörper (20,31,48,53), which indicates that endocytic vesicles cluster in the hyphal tip. Indeed, endocytic recycling via early endosomes is essential for proper hyphal morphology and pathogenicity in the corn smut Ustilago maydis (33,134 [also see below]).…”
Section: Endocytosis and Hyphal Growthmentioning
confidence: 99%
“…An important breakthrough was the observation that the endocytosis marker dye FM4-64 rapidly stains vesicles within the Spitzenkörper (Fig. 1b to d) (18,32,35), not only providing evidence for the interconnection of endocytic and secretory pathways but demonstrating the dye's utility for visualizing and analyzing Spitzenkörper behavior in wild-type and mutant strains (31,32).…”
Section: Microscopymentioning
confidence: 99%